Family support as reflective practice - Dolan, Pat, 1958-; Canavan, John, 1967-; Pinkerton, John, 1953- (Jessica Kingsley Publishers, 2006)
Family support is an increasingly important strategic approach to welfare services for children and families. This resource for all professionals engaged covers core issues in family support. These include the importance of community, the role of statutory and voluntary agencies, youth advocacy, culturally appropriate family support, child protection, disability services and effective means of evaluation. Providing a combination of clear theoretical frameworks and practical guidance, with clear 'how to' messages and a strong emphasis on evaluation, this book will be essential to social workers.